2000
DOI: 10.1046/j.1365-2958.2000.02070.x
|View full text |Cite
|
Sign up to set email alerts
|

DNase I homologous residues in CdtB are critical for cytolethal distending toxin‐mediated cell cycle arrest

Abstract: SummaryCytolethal distending toxins (CDTs) block cell division by arresting the eukaryotic cell cycle at G2/M. Although previously not recognized in standard BLAST searches, a position-specific iterated (PSI) BLAST search of the protein data bank using CDT polypeptides as query sequences indicated that CdtB bears significant position-specific homology to type I mammalian DNases. The PSI-BLAST sequence alignment reveals that residues of DNase I involved in phosphodiester bond hydrolysis (His134 and His252) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
348
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(372 citation statements)
references
References 38 publications
20
348
0
4
Order By: Relevance
“…Recently, two research groups indicated independently that CDT has structural homology to human DNase I and suggested that CDTB is an active component of the CDT complex acting as a DNase. In support of this, E. coli CDTB has been demonstrated to possess nicking activity toward purified plasmid in vitro (14). These findings have raised the possibility that CDTB directly damages chromosomal DNA, which results in the onset of phosphorylation of the checkpoint control cascade described above.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Recently, two research groups indicated independently that CDT has structural homology to human DNase I and suggested that CDTB is an active component of the CDT complex acting as a DNase. In support of this, E. coli CDTB has been demonstrated to possess nicking activity toward purified plasmid in vitro (14). These findings have raised the possibility that CDTB directly damages chromosomal DNA, which results in the onset of phosphorylation of the checkpoint control cascade described above.…”
mentioning
confidence: 75%
“…Among them, all but Glu 66 are located in the C-terminal half of the CDTB molecule. Previously, Elwell and Dreyfus demonstrated that His 154 , Asp 229 , Asp 260 , and His 261 of E. coli CDTB are essential for the activity, but Glu 66 is not (14). Taken together with the notion that N-terminal 48 -124 aa plays a role as a domain for nuclear transport, we hypothesized that CDTB forms a two-domain structure composed of the N-terminal domain and C-terminal genotoxic activity domain.…”
Section: Cdtb Is Composed Of An N-terminal Domain For Nuclear Transpomentioning
confidence: 89%
See 2 more Smart Citations
“…Eukaryotic cells that are sensitive to the toxin are usually arrested at the G 0 /G 1 or G 2 /M phase of the growth cycle (Comayras et al, 1997;Whitehouse et al, 1998;Cortes-Bratti et al, 1999;Shenker et al, 1999). CDT triggers the block in cell-cycle progression through the action of a DNase I-like nuclease (CdtB) that causes double-strand breaks in the host-cell DNA (Elwell & Dreyfus, 2000;LaraTejero & Galán, 2000;Cortes-Bratti et al, 2001;Frisan et al, 2003;Hassane et al, 2003).…”
Section: Introductionmentioning
confidence: 99%